2022
DOI: 10.1111/jfpp.16986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV‐C treatments on quality and browning‐related enzyme activity of fresh‐cut eggplant ( Solanum melongena L.) during cold storage

Abstract: The effect of UV‐C (1, 2, 5, and 10 kJ/m2) on sensory attributes, browning index (BI), ascorbic acid (AA), total phenolic compounds, and browning‐related enzymes (i.e., polyphenol oxidase, PPO; phenylalanine ammonia lyase, PAL) of fresh‐cut eggplants throughout 10 days at 4°C was studied. Untreated samples were used as control. Treatments with 5 and 10 kJ/m2 presented higher values of PPO activity and BI, with a loss of 50% and 30% of AA and phenols compared with the control, and sensory quality fewer than 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
4
1
Order By: Relevance
“…Moreover, Lemos et al (2022) evaluated the effect of UV on fresh-cut eggplants. They reported that the PPO activity in UV-treated eggplants was between 5.98 and 6.38 AU/min/mg protein [35]. These results were lower than the results obtained in the present work, which could be due to the better efficiency of UV in the deactivation of PPO than agronomic treatments.…”
Section: Colorimetric Parameterscontrasting
confidence: 97%
See 2 more Smart Citations
“…Moreover, Lemos et al (2022) evaluated the effect of UV on fresh-cut eggplants. They reported that the PPO activity in UV-treated eggplants was between 5.98 and 6.38 AU/min/mg protein [35]. These results were lower than the results obtained in the present work, which could be due to the better efficiency of UV in the deactivation of PPO than agronomic treatments.…”
Section: Colorimetric Parameterscontrasting
confidence: 97%
“…One of the main problems with eggplants is enzymatic browning on the cut surface, which limits the eggplant's shelf life [35]. Table 2 shows the color properties of fresh-cut eggplants, fertilized with chicken manure, which were exposed to air over time at room temperature.…”
Section: Colorimetric Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was also observed in other vegetables products. Lemos et al (2022) observed inhibition of PPO activity by low UV‐C doses (1 and 2 kJ/m 2 ) in fresh‐cut eggplant, while highest doses increased its activity up to control samples during storage. Probably, the irradiation with low doses could modulate a signaling pathway which leads in a decrease or stabilization of the PPO activity (Lemos et al, 2022) maintaining the total polyphenol content during storage as it was shown in Section 3.1.2 in the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Non-enzymatic browning reactions, particularly the Maillard reaction, have been reported as notable contributors [ 33 , 34 ]. Furthermore, some studies have reported the important roles of other antioxidants, various enzymes, and environmental factors such as temperature and pH, along with specific storage conditions, as influencing factors in the browning of eggplants [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%